Probable Value for the Next Sunspot Minimum - Silbergleit, Virginia Mabel (2014)
Gumbel first distribution is applied to smoothed monthly mean sunspot numbers for solar cycles 10 to 24. According to that, the next minimum for solar cycle 24-25 transition would be the deepest solar minimum of the last 150 years. This study provides an additional insight about changes in the Sun which are currently happening.